Designing and developing a model for quality management and best practice for the Translation Unit of the Pan African Parliament - Rahmtalla, Mohamed Mustafa Ahmed (My University, 2017)
Using the Translation Unit of the Pan African Parliament (PAP-TU) as a case study, this research set out to find a comprehensive method for assuring the quality of the translation services of non-commercial organisations. This aim is fulfilled through achieving two objectives: firstly, assessing the current situation of the PAP-TU; secondly, building a model for quality management and best practice to assure the quality of the services of the PAP-TU. In addition to solving the problem at hand, this research is motivated by exploring new areas of translation studies, engaging in the ongoing debate around the topic and contributing to the body of knowledge in this lessexplored area. To achieve the objectives of the research, a qualitative empirical study was designed to examine the correlation between ‘adopting a quality management model’ and ‘assuring translation quality’. An action research method was used to inform the outcome of the study and to provide a framework for its design. For achieving the first objective, a case study research method was used to assess the current situation of the PAP-TU. The data was collected through interviews, fieldwork observation and archival research techniques; a grounded theory technique was used for analysing the data. A modelling research method was used for achieving the second objective: creating a quality model for the PAP-TU. The study finds that the current approaches to translation quality are unable to assure the quality of the translation services of non-commercial organisations and that there is a need for a more holistic model. The main outcome of the study is the creation of a quality model for the PAPTU. The study has reached many conclusions; the most important of which are: firstly, there is a shift in the translation field from considering translation as a craft or art to professionalization and industrialisation; secondly, the study confirms the gap between translation theory and practice. The study recommends conducting more research in the field of translation quality management as a growing branch of translation studies and in freelancing as an important type of employment for translators. The study also recommends designing translators’ training programmes after studying the market to address the latest needs and trends in the market.
A Dissertation Submitted to the Faculty of Humanities, University of Witwatersrand in Fulfilment for the Award of the Degree of Master of Arts in Translation and Interpreting Studies, March 2017
Keywords: African Union; African Union; Translating and interpreting--Africa; Conflict management--Africa; Africa--Politics and government